Urban resilience supported by technology in disaster management and prevention - Nemer, Luciana; Costa , Mariana de Melo; Silva, Felipe Gustavo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2026)
Objective – To investigate how urban resilience can be strengthened in disaster management and prevention, focusing on the application of City Information Modeling (CIM) and digital technologies.Methodology – Adopts a qualitative approach based on a literature review, case study, and comparative analysis. It examines two disasters in Brazil, the 2024 floods in Porto Alegre and the ground subsidence in Maceió caused by rock salt mining, alongside international experiences in Venice and Helsinki.Originality/Relevance – The research addresses a theoretical gap in the Brazilian context by integrating digital technologies, urban resilience, and disaster mitigation, contributing to academic discussions on the strategic role of CIM in urban risk management.Results – The findings indicate that urban resilience relies on the integration of information modeling technologies, effective governance structures, and community participation, while also revealing challenges related to limited investment and insufficient technical capacity.Theoretical/Methodological Contributions – The article advances the understanding of CIM as a support tool for disaster analysis, prevention, and management, providing insights for its application in urban environments.Social and Environmental Contributions – The results highlight the potential of digital technologies to reduce socio-environmental impacts, support public policy formulation, and strengthen management strategies.
Keywords: Urban Resilience; City Information Modeling (CIM); Environmental Disasters